Comprehensive Extraction and Biological Activities of Mycosporine-like Amino Acids and Glyceroglycolipids Extracts from Two Macroalgae Ecklonia kurome and Ulva lactuca - Xin Wei; Xiaoqi Hu; Tianhuan Li; Yuxiang Li; You Yu; Xiujing Jiang; Haonan Wang; Jie Yang; Xue Jiao; Xinghu Zhou; Yingying Sun (Foods)
Mycosporine-like amino acids (MAAs) and glyceroglycolipids have promising applications in various fields, but limited research exists on their simultaneous extraction from macroalgae. This study optimized the key parameters (liquid–solid ratio, extraction temperature and extraction time) in the extraction of MAAs and glyceroglycolipids from Ecklonia kurome and Ulva lactuca using single factor and response surface experiments. The yields of MAAs from E. kurome and U. lactuca were 169.71 mg/g and 177.33 mg/g, respectively, while glyceroglycolipids were extracted from the residue with yields of 163.51 mg/g and 213.45 mg/g, respectively. Both extracts showed concentration-dependent antioxidant activities, with the MAAs extracted from U. lactuca demonstrating the strongest effect. The addition of MAA extract to flaxseed oil significantly reduced oxidation rancidity, highlighting its potential as a natural antioxidant for oils. The glyceroglycolipid extract from E. kurome exhibited significant moisture absorption, and a water-retaining agent prepared from this extract showed excellent moisture retention and resistance to high temperatures, freezing, and pressure. A silica gel column chromatography method confirmed the presence of MGDG in the purified glyceroglycolipid extract. These findings suggested that E. kurome and U. lactuca can be converted into high-value-added compounds with potential applications in food, cosmetics, and pharmaceuticals.